PENINGKATAN KUALITAS PRODUKSI USAHA WEDANG UWUH UNTUK MENINGKATKAN EKONOMI MASYARAKAT DUSUN KERTEN IMOGIRI BANTUL - Sri Suryaningsum; Anies Siti Hartati (Universitas Muhammadiyah Surakarta, 2018)
The business of wedang uwuh can help the people's economy in Dusun Kerten, Imogiri. To support the improvement of its economy, there must be improvement of production and marketing quality in wedang uwuh. This research is done by using the method of observation and interview to the source. The result of this research is the improvement of production quality by choosing quality raw materials, drying process, making expiration date and making wedang uwuh in the form of brew. In terms of marketing enhancement, it is done by making regular scientific publications about wedang uwuh development and improving regular sachets packaging to more attractive packaging.